2017
DOI: 10.21713/2358-2332.2017.v14.1375
|View full text |Cite
|
Sign up to set email alerts
|

Formação do orientador de pesquisas acadêmicas: um estudo bibliográfico nacional e internacional

Abstract: ResumoEste trabalho objetiva mapear quantitativamente e identificar temáticas associadas à formação do orientador, por meio de um amplo levantamento bibliográfico nacional e internacional. Apesar da centralidade do orientador para o desenvolvimento de pesquisas, sua formação é vista como espontânea e individual, permanecendo à margem de ações e investigações na universidade. Identificamos 237 pesquisas nacionais e internacionais sobre o tema, que nos permitiram construir dez categorias temáticas. Os resultados… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
(27 reference statements)
0
4
0
3
Order By: Relevance
“…The relationship established during the guidance is able to affect the likelihood of the student continuing their education, as well as being linked to the quality of the activities developed in stricto sensu. The discordances found by the students regarding their advisors may be due to a lack of professionalization and clear guidance concerning the advisor's role in the Brazilian university environment (Massi & Giordan, 2017). It is suggested that post-graduate programs monitor and evaluate the quality of their guidance by consulting the students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship established during the guidance is able to affect the likelihood of the student continuing their education, as well as being linked to the quality of the activities developed in stricto sensu. The discordances found by the students regarding their advisors may be due to a lack of professionalization and clear guidance concerning the advisor's role in the Brazilian university environment (Massi & Giordan, 2017). It is suggested that post-graduate programs monitor and evaluate the quality of their guidance by consulting the students.…”
Section: Discussionmentioning
confidence: 99%
“…The guidance process and the relationship between the advisor and student are investigated in the literature from various perspectives. Nóbrega (2018) addressed the relationship in academic guidance processes and the formal role of the advisor; Falaster et al (2017) discussed the impact of the guidance on the future publications of PhD students; Massi and Giordan (2017) addressed the advisor's training; and Leite and Martins (2006) analyzed the influences of the advisor-student relationship on the production of theses and dissertations in business and accounting courses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Walker and Thomson's research (2010) on the importance of the activities of research groups and their collaborative networks for the constitution of a "pedagogy or didactic of guidance" was decisive for studies on the training of advisors. On this matter, Massi and Giordan (2017) conducted a research to identify themes associated with the training of advisors in a wide national and international bibliographic survey. In more 1 Since the early 2000s, we have been developing research, funded by CNPq, and added new references and theoretical and empirical knowledge based on Bahia Horta (2012, p. 13), who pointed out, in the preface of A bússola do escrever : "By valuing and putting in place the noble activity of guidance, in a way rowing against the current, this publication can help break this vicious cycle, thus providing an invaluable contribution to graduate studies in our country.…”
Section: The Relationship Between Advisor and Supervising Student: Fr...mentioning
confidence: 99%
“…Recentemente, problemas como a maior exigência de produtividade, preocupações éticas na condução e divulgação da pesquisa e a saúde mental dos pesquisadores tiveram maior visibilidade aumentando a preocupação com a sua formação e atuação (Bianchetti & Quartiero, 2010;Alves, Espindola, & Bianchetti, 2012). O orientador de pesquisas acadêmicas têm sido investigado internacionalmente (Massi & Giordan, 2017), com maior ênfase a partir de 2005. Embora seja um tema marginal de diversas áreas de estudo, o reconhecimento de sua importância e o esforço para que a atuação dos orientadores saia da esfera individual e artesanal para assumir aspectos mais formativos e profissionais é unânime na literatura (Massi & Giordan, 2017).…”
Section: Introductionunclassified